Chemopreventive effect of Phyllanthus polyphyllus against N-nitrosodiethylamine induced liver tumors in wistar rats - Naina Mohamed Pakkir Maideen; Ravichandiran Velayutham; Gobinath Manavalan (International Journal of Phytomedicine, 2011)
The aim of the study is to evaluate the chemopreventive effect of methanol extract of Phyllanthus polyphyllus (MPP) against N-nitrosodiethylamine (DEN, 200mg/kg) induced experimental liver tumors in male wistar rats. Administration of Phyllanthus polyphyllus (200 and 400mg/kg) effectively suppressed liver tumor induced by DEN as revealed by decrease in DEN induced elevated levels of mitochondrial lipid peroxidation (LPO), deoxy ribonucleic acid (DNA), ribo nucleic acid (RNA) and liver weight. The extract produced an increase in mitochondrial enzymatic antioxidants (Superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) and non enzymatic antioxidants (Reduced Glutathione (GSH)) levels when compared to liver tumor bearing animals. Our data suggest that MPP may extend its chemopreventive effect by modulating the levels of mitochondrial lipid peroxidation, DNA and RNA and liver weight and augmenting mitochondrial antioxidant defense system.